THE EFFECTIVENESS OF MIND-MAPPING TOWARDS STUDENTS’WRITING SKILL - Firman, Edi; Imran, Fathurrahman; Sandiarsa, K. Dedy (Jurnal Ilmiah IKIP Mataram, 2018)
This research was intended to analyze the effect of mind mapping towards students writing skill at the second semester students of FPBS IKIP Mataram in academic year 2015/2016. This study was quasi experimental research, where the sample was cluster randomly selected with the total number of sample was 65 students which were divided into 2 classes; 29 students were in the control group and there were 36 students belong to experimental group. In order to collect the research data, the writer used writing test to comprehend the studentsâ€™ ability in managing text based on mind mapping concept. After the data was obtained, then it was analyzed by applying descriptive statistical analysis and inferential analysis. Regarding to the data analysis it was found that the studentsâ€™ ability before treatment was 69.72 in the significant level 95%. On post-test data analysis, the students mean writing ability increased into 77.22. The inferential analysis or hypothesis testing also proved that the t-test was higher than t-table in the significant level 95% (Î± =0.05) and degree of freedom 63 (4.158 > 2.000) with Ï value (sig.) 0.00 < 0.05. It was clearly claimed that the alternative hypothesis (Ha) which stated that mind-mapping was effective towards students writing at second semester students of FPBS IKIP Mataram in academic year 2015/2016 was accepted and the null hypothesis (Ho) that said main-mapping is not effective toward students writing at second semester students of FPBS IKIP Mataram in academic year 2015/2016 was rejected. Those data evidently proved that mind mapping was effective towards students writing especially at second semester students of FPBS IKIP Mataram in academic year 2015/2016.